2019
DOI: 10.1101/607655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices (KAPs) and risk factors of brucellosis at the human-animal interface in the Nile Delta, Egypt

Abstract: 36 Background: Brucellosis is a highly contagious zoonosis affecting human and almost all domestic 37 species. It is a multi-burdens disease leading to severe economic losses due to disability in humans in 38 addition to abortion, infertility and reduced milk production in animals. An Important element for 39 effective prevention and control of brucellosis is to improve knowledge, attitude and practices of the 40 community. 41 Objective(s): This study aimed to assess the knowledge, attitudes and practices (KAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…In Tanzania, low knowledge, perception and practices towards brucellosis prevention were reported (Ntirandekura et al 2018 ). Another study carried out in Nile Delta, Egypt (Abd El-Wahab et al 2019 ) showed that more than two-thirds (67.4%) of the participants had not heard about brucellosis and in Rwanda 57.5% were unaware of brucellosis (Ndazigaruye et al 2018 ). In contrast to our findings, some studies on brucellosis knowledge reported a 100.0% awareness in Jordan (Musallam, Abo-Shehada & Guitian 2015 ) whilst 99.3% of the respondents had heard about brucellosis in Uganda (Kansiime et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, low knowledge, perception and practices towards brucellosis prevention were reported (Ntirandekura et al 2018 ). Another study carried out in Nile Delta, Egypt (Abd El-Wahab et al 2019 ) showed that more than two-thirds (67.4%) of the participants had not heard about brucellosis and in Rwanda 57.5% were unaware of brucellosis (Ndazigaruye et al 2018 ). In contrast to our findings, some studies on brucellosis knowledge reported a 100.0% awareness in Jordan (Musallam, Abo-Shehada & Guitian 2015 ) whilst 99.3% of the respondents had heard about brucellosis in Uganda (Kansiime et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to a study conducted in Kenya which recorded 96% raw milk consumption in a year (Obonyo & Gufu 2015 ). In another study conducted in Nile Delta, Egypt, drinking raw fresh milk was an uncommon practice owing to the awareness of associated hazards (Abd El-Wahab et al 2019 ). In this present study, the social-cultural practice was the main reason for low or no raw milk consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis may be transmitted from wild animals to domestic animals and ultimately to human beings (Cutler et al 2005 ). Moreover, a little knowledge on the disease and its transmission among livestock handlers negatively reflect their attitude and practice towards the disease control strategies (El-Wahab et al 2019 ).…”
Section: Disease Spectrum In Humansmentioning
confidence: 99%
“…Brucella species are among those pathogenic bacteria which have propensity to adapt to new host and they can either be naturally transmitted to their primary hosts by direct or indirect contact or sometimes inadvertently to other susceptible hosts (Moreno 2014 ). Mixed farming of cows, buffaloes, sheep and goats has increased the risk of brucellosis where small ruminants act as primary hosts for B. melitensis and cattle as spillover host (El-Wahab et al 2019 ). In India, brucellosis causes an average loss of US$18.2 per buffalo followed by 6.8 per cattle, 0.7 per sheep, 0.6 per pig and 0.5 per goat (Singh et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors were identified including animal species, age, and pregnancy conditions as well as the occurrence of reproductive disorders. Furthermore, some environmental conditions, including milk storage and hygienic conditions, herd size, study area, and breeding approaches represent other key factors (Dadar et al 2019b;Deka et al 2018;El-Wahab et al 2019;Ness et al 2017;Ning et al 2013;Omer et al 2000;Proch et al 2018). However, the incidence of brucellosis in different hosts and countries is directly associated with eradication and control programs in livestock that should be implemented by national veterinary services such as vaccination and "test and slaughter" policy.…”
Section: Brucella Spp Shedding In Milkmentioning
confidence: 99%